Beyond fertility preservation: role of the oncofertility unit in the reproductive and gynecological follow-up of young cancer patients. Issue 8 (24th July 2019) - Massarotti, Claudia; Scaruffi, Paola; Lambertini, Matteo; Sozzi, Fausta; Remorgida, Valentino; Anserini, Paola
Abstract: STUDY QUESTION: Are there reasons that motivate young cancer survivors to ask for follow-up visits at an oncofertility unit? SUMMARY ANSWER: Cancer survivors request oncofertility follow-up visits for the management of treatment-related side effects or ovarian reserve evaluation, even if not (or not yet) wishing for a pregnancy. WHAT IS KNOWN ALREADY: Personalised oncofertility counselling before gonadotoxic therapies is considered standard of care for young women with newly diagnosed cancer. However, the long-term follow-up of these patients in an oncofertility unit is not described in the literature other than for the use of cryopreserved material. STUDY DESIGN, SIZE, DURATION: We retrospectively examined rates and reasons for the first follow-up visits of 154 consecutive young female cancer patients (age range: 18–40 years) who underwent a pre-treatment consultation between January 2012 and June 2017. Demographic and clinical data were collected, as well as information about the chosen fertility preservation method, if any. PARTICIPANTS/MATERIALS, SETTING, METHODS: Rates and reasons for follow-up visits were collected and expressed as percentages. Different reasons were examined in the whole cohort and stratified for type of malignancy. Possible predictive factors for return to the follow-up visit (age, nulliparity, presence of a partner, neoplasm, having cryopreserved material) were investigated through logistic regression. MAIN RESULTS AND THE ROLE OF CHANCE: Out of 154 patients, 74 returned to the oncofertility unit (48.1%) for a follow-up visit. The first visit was requested mostly at the end of anticancer therapies (51.3% versus 40.5% during therapies and 8.1% after cancer relapse). Among these patients, only 10.8% returned for the first time because they were actively desiring a pregnancy. For the others, the most common reasons for consultations were management of gynecological adverse effects of therapies (29.7%) and evaluation of ovarian reserve not linked to an immediate desire for a pregnancy (39.2%). Other patients asked for contraception (4.1%), menopause counselling (5.4%), or new fertility preservation counselling because of cancer relapse (10.8%). None of the examined factors were significantly predictive of return to the oncofertility unit. LIMITATIONS, REASONS FOR CAUTION: These findings represent the experience of a single centre. A longer duration of follow-up would be needed to provide more precise information on this regard. WIDER IMPLICATION OF THE FINDINGS: The role of an oncofertility unit should not be limited to proposing fertility preservation procedures. In the management of young adult cancer patients, the reproductive medical specialist should be considered a key figure not only before but also during and after anticancer treatments to explore salient aspects of gynecological and reproductive health. STUDY FUNDING/COMPETING INTEREST(S): This research did not receive any specific funding. M.L. served as a consultant for Teva and received honoraria from Theramex outside the submitted work. The other authors declare no conflict of interest. TRIAL REGISTRATION NUMBER: N.A.